Identification of Chalcone Derivatives as Inhibitors of Leishmania infantum Arginase and Promising Antileishmanial Agents - Garcia, Andreza R.; Oliveira, Danielle M. P.; Jesus, Jessica B.; Souza, Alessandra M. T.; Sodero, Ana Carolina R.; Vermelho, Alane B.; Leal, Ivana C. R.; Souza, Rodrigo Octavio M. A.; Miranda, Leandro S. M.; Pinheiro, Anderson S.; Rodrigues, Igor A. (Frontiers in Chemistry, 2021)
Arginase catalyzes the hydrolysis of L-arginine into L-ornithine and urea, acting as a key enzyme in the biosynthesis of polyamines. Leishmania growth and survival is dependent on polyamine biosynthesis; therefore, inhibition of Leishmania arginase may be a promising therapeutic strategy. Here, we evaluated a series of thirty-six chalcone derivatives as potential inhibitors of Leishmania infantum arginase (LiARG). In addition, the activity of selected inhibitors against L. infantum parasites was assessed in vitro. Seven compounds exhibited LiARG inhibition above 50% at 100 µM. Among them, compounds LC41, LC39, and LC32 displayed the greatest inhibition values (72.3 ± 0.3%, 71.9 ± 11.6%, and 69.5 ± 7.9%, respectively). Molecular docking studies predicted hydrogen bonds and hydrophobic interactions between the most active chalcones (LC32, LC39, and LC41) and specific residues from LiARG’s active site, such as His140, Asn153, His155, and Ala193. Compound LC32 showed the highest activity against L. infantum promastigotes (IC50 of 74.1 ± 10.0 µM), whereas compounds LC39 and LC41 displayed the best results against intracellular amastigotes (IC50 of 55.2 ± 3.8 and 70.4 ± 9.6 µM, respectively). Moreover, compound LC39 showed more selectivity against parasites than host cells (macrophages), with a selectivity index (SI) of 107.1, even greater than that of the reference drug Fungizone®. Computational pharmacokinetic and toxicological evaluations showed high oral bioavailability and low toxicity for the most active compounds. The results presented here support the use of substituted chalcone skeletons as promising LiARG inhibitors and antileishmanial drug candidates.